UVA Induced Oxidative Stress Was Inhibited by Paeoniflorin/Nrf2 Signaling or PLIN2 - Lu, Yan-Song; Jiang, Yuan; Yuan, Jin-ping; Jiang, Shi-Bin; Yang, Yang; Zhu, Pei-yao; Sun, Yu-zhe; Qi, Rui-qun; Liu, Tao; Wang, He-Xiao; Wu, Yan; Gao, Xing-Hua; et al. (Frontiers in Pharmacology, 2020)
Photodamages caused by UVA radiation induced oxidative injuries are closely related to photoaging and skin cancer. Paeoniflorin (PF), extracted from the root of Paeonia lactiflora, has been reported to be an effective antioxidant. PLIN2, known as adipose differentiation-related protein, has been previously involved in the regulation of oxidative stress. In this study, we were sought to investigate the photo-protective property of PF and PLIN2 in UVA-radiated human dermal fibroblasts (HDFs). HDFs were pre-treated with PF (800 μM) followed by UVA radiation (22.5 J/cm2). MTS activity, cell apoptosis, ROS, MDA, and SOD were detected, respectively. The expressions of Nrf2, HO-1, NQ-O1, and PLIN2 were determined using RT-qPCR or western blot. Nrf2 was silenced by siRNA, and PLIN2 was overexpressed via lentiviral transduction. Comparing to the UVA radiation, PF pre-treatment could prominently increase the MTS activity, decrease cell apoptosis, reduce the generations of ROS and MDA, increase the activity of SOD and increase the expression of Nrf2 and its target genes HO-1 and NQ-O1. When Nrf2 was knocked down, PF lost above protective properties. In addition, UVA induced oxidative stress led to upregulation of PLIN2 and the latter could be decreased by PF. Overexpression of PLIN2 improved MTS activity and reduced MDA level in HDFs. The combination of PLIN2 overexpression and PF pre-treatment corporately inhibited UVA-induced injury. Besides, we also found that PF and PLIN2 had a compensatory protection against UVA induced oxidative stress. In conclusion, our study demonstrated that UVA induced photodamages could be inhibited by PF via Nrf2/HO-1/NQ-O1 signaling pathway or by PLIN2, and the combination of PLIN2 overexpression and PF played additive effects against UVA-related oxidative stress.